2016
DOI: 10.5114/pjp.2016.63779
|View full text |Cite
|
Sign up to set email alerts
|

Cystoisosporiasis-related human acalculous cholecystitis: the need for increased awareness

Abstract: Cholecystitis is one of the common surgical indications affecting human beings in many countries. A variety of infectious agents can be associated with acute or chronic acalculous cholecystitis, especially in HIV/AIDS patients. In this investigation, the authors aim to describe two cases of histologically and molecularly documented cystoisosporiasis (syn. isosporiasis) as the cause of chronic acalculous cholecystitis in two immunodeficient patients. During microscopic examinations of more than 2500 diarrheic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…was 3/3 (100%) in 10-19 age group and 1/2 (50%) among ages 20-39 years. As regards to I. belli, it was the least common species with 1/1 (100%) occurrence in age group 40-69 years, ½ (25%) in ages 20-39 and none in children 0/3 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). There was no significant relationship between I. belli and age (P = 0.15).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…was 3/3 (100%) in 10-19 age group and 1/2 (50%) among ages 20-39 years. As regards to I. belli, it was the least common species with 1/1 (100%) occurrence in age group 40-69 years, ½ (25%) in ages 20-39 and none in children 0/3 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). There was no significant relationship between I. belli and age (P = 0.15).…”
Section: Resultsmentioning
confidence: 95%
“…From Table 2.out of the study group it was shown that the distribution of coccidian parasites was greater in females with an occurrence of 7.1% as compared to 2.4% among the male population. For both Cryptosporidiosis and I. belli, univariate analysis did not show any significant differences in infection between males and females, (P = 0.19), however, HIV seropositive children with diarrhea (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) were three times more likely to be infected with coccidian parasites than the HIV seropositive age groups 20-39 and 40-69 years i.e. 13.6%, 3.4% and 3.3% respectively.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…5 Cystoisospora in the gallbladder and biliary tract has been reported in both immunocompetent and immunosuppressed individuals. [6][7][8][9][10][11][12] Recently, the identity of these structures in the gallbladder has been questioned based on negative nucleic acid studies using primers directed against C belli. 13 To understand the prevalence of this histologic finding, we examined cholecystectomy specimens from a pediatric institution and performed electron microscopy from paraffin-embedded specimens to investigate the ultrastructure of the eosinophilic structures that have been attributed to Cystoisospora, with the hypothesis that parasitic inclusion would be demonstrable by electron microscopy, similar to previous examples of Cystoisospora.…”
mentioning
confidence: 99%